2017
DOI: 10.1007/s11104-017-3486-4
|View full text |Cite
|
Sign up to set email alerts
|

Green manure effects on zinc and cadmium accumulation in wheat grains (Triticum aestivum L.) on high and low zinc soils

Abstract: Background and aims Zinc (Zn) deficiency is a global problem in human nutrition due to imbalanced diets based on staple foods of low Zn contents. This study investigated the potential of using clover (Trifolium alexandrinum L.) and mustard (Sinapis alba L.) green manure crops to increase soil Zn uptake by wheat (Trifolium aestivum L.) without enhancing cadmium (Cd) accumulation. Methods A factorial pot experiment with wheat was performed with three green manure treatments (clover, mustard or no green manure) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
2
9
3
Order By: Relevance
“…In line with this and in agreement with several other studies(Cakmak et al 2010;Kutman et al 2010), we found positive correlations between wheat shoot and grains N and Zn and Cd concentrations (Table7). Similarly as inGrüter et al (2017b), we found more wheat root and shoot (excluding grains) biomass production in the LOW Zn soil than in the HIGH Zn soil, which may partly be atttributed to the poor soil structure of the HIGH Zn soil (observed by high soil density and distribution of the roots along the pot walls). Low aggregate stability was con rmed by a low Ca content (1.68 g kg − 1 ), which is known to improve aggregate stability through building Ca bonds between clay and humus particles(Blume et al 2016).…”
supporting
confidence: 84%
“…In line with this and in agreement with several other studies(Cakmak et al 2010;Kutman et al 2010), we found positive correlations between wheat shoot and grains N and Zn and Cd concentrations (Table7). Similarly as inGrüter et al (2017b), we found more wheat root and shoot (excluding grains) biomass production in the LOW Zn soil than in the HIGH Zn soil, which may partly be atttributed to the poor soil structure of the HIGH Zn soil (observed by high soil density and distribution of the roots along the pot walls). Low aggregate stability was con rmed by a low Ca content (1.68 g kg − 1 ), which is known to improve aggregate stability through building Ca bonds between clay and humus particles(Blume et al 2016).…”
supporting
confidence: 84%
“…3 and 10 mg Zn kg −1 , respectively), considered as critical for wheat growth (White 1993). Contrasting results were obtained in a recent pot experiment conducted by Grüter et al (2017b) using the same two soils, as well as the same clover and wheat variety, but under different growing conditions (climate chamber with higher air temperature and a different lighting system). In their study, the incorporation of clover green manure increased aboveground wheat Zn uptake by almost a factor of two in the LOW Zn and of five in the HIGH Zn soil.…”
Section: Soil X-ray Irradiation Increased Soil Mineral N Wheat Growth and Element Accumulationmentioning
confidence: 71%
“…R. leguminosarum was also inoculated in LOW Zn where no green manure was grown. The HIGH Zn Table 1 Physicochemical and biological properties of the two soils used in this study Soil analyses were performed before green manure sowing as an initial soil characterization a Apart from total soil N, DGT extractable Zn and Cd, basal soil respiration and microbial C and N biomasses, the rest of the soil parameters given in this table was obtained from Grüter et al (2017b) b IUSS Working Group WRB (2014) c Below limit of detection (< LOD) d For LOW Zn, the DTPA extractable Zn was below 0.5 mg kg −1 , commonly considered as the Zn deficiency threshold (Cakmak et al 1996 soil was not inoculated with this rhizobium as preliminary tests highlighted infectious potential of this soil. Nodules were found on clover roots in both soils after 6 weeks of growth.…”
Section: Green Manure Growth and Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in plant Zn can be achieved through fertilizer application (soil and/or foliar) and appropriate crop rotation (De Valença, Bake, Brouwer, & Giller, 2017). Green manure applications increase Zn content in wheat grain, and nutrient release follows decomposition rate (Gruter, Meister, Schulin, & Tandy, 2018). Soil applications of Zn fertilizer can raise grain Zn concentration in wheat three or four-fold (Cakmak, 2008), and one-off soil amendments give persistent benefits in many soil types.…”
Section: 11) Agronomic Zn Biofortificationmentioning
confidence: 99%